Pemahaman Bidan Terkait Peraturan Daerah No. 5 Tahun 2014 tentang Inisiasi Menyusui Dini dan ASI Eksklusif - Dhita Aulia Octaviani; Ulfah Musdalifah (Universitas Faletehan, 2022)
Semarang Regency, Central Java Province was the regency/city that ranked fourth lowest in the coverage of exclusive breastfeeding, which was 50.7% in 2018, although there was already regulatory support in the form of Regional Regulation Number 5/2014 concerning early initiation of breast feeding (EIBF) and exclusive breastfeeding. This study aimed to describe the implementation of Regional Regulation No. 5/2014 on EIBF and exclusive breastfeeding among midwives in Semarang Regency and analyze the influencing factors. This research was quantitative with analytical observational design and cross-sectional approach. The number of samples was 38 midwives in Semarang Regency who met the inclusion criteria. The data collection was carried out using a questionnaire that had been tested for its validity. The results of the study showed that there was a relationship of education, length of work, implementation of Regional Regulation No. 5 of 2014 with the practice of midwives on EIBF and exclusive breastfeeding. However, the midwives’ understanding of the provisions contained therein needs to be further improved, especially the information of EIBF and exclusive breastfeeding that should be delivered from the times of pregnancy examination until the period of exclusive breastfeeding is over. The better the midwives’ understanding of the contents of Regional Regulation No. 5 2014 concerning EIBF and Exclusive Breastfeeding, the midwives' practice of implementing EIBF and exclusive breastfeeding also got better.